レンゾク フロー シキ シツリョウ ブンセキケイ ヲ モチイタ タイキチュウ メタン ノ タンソ ドウイタイ ヒ ノ コウセイド ソクテイ - 森本, 真司; モリモト, シンジ; 青木, 周司; アオキ, シュウジ; 中澤, 高清; ナカザワ, タカキヨ; Morimoto, Shinji; Aoki, Shuji; Nakazawa, Takakiyo (2009)
P(論文) メタン(CH_4)濃縮装置とガスクロマトグラフ-燃焼炉-同位体比質量分析計を用いた大気中メタンの炭素同位体比(δ^(13)CH_4)分析システムを開発した.本システムは,100 mlの大気試料(標準状態で0.18μlのCH_4)を用いて0.07‰の再現性でδ^(13)CH_4を分析することが可能である.2002年から2008年にかけて,空気ベースCH4標準ガスのδ^(13)CH_4を繰り返し分析することにより,δ^(13)CH_4分析値の信頼性を確認した.国立極地研究所において大気中のCH_4濃度とδ1^(13)CH_4の日変化を観測し,両者の関係からCH4 濃度の変動原因について情報が得られることを確認した. A high-precision measurement system for the carbon isotope ratio of atmospheric CH4 (δ^(13)CH_4) was developed using a pre-concentration device for CH4 and a gas chromatograph-combustion-isotope ratio mass spectrometer (GC-C-IRMS). The measurement system required 100 mlSTP of an atmospheric air sample, corresponding to approximately 0.18μlSTP of CH_4, to determine the δ^(13)CH_4 value with a reproducibility of 0.07‰. Replicated analyses of a CH_4-in-air standard gas during the period from 2002 to 2008 indicated that the value of δ^(13)CH_4 measured by this system was consistent within the measurement reproducibility. To evaluate the δ^(13)CH_4 measurement system, thus developed, diurnal variations of the atmospheric CH_4 concentration and δ^(13)CH_4 were observed in the northern part of the Tokyo metropolitan area. From the relationship between the CH_4 concentration and δ^(13)CH_4, dominant sources of the observed CH4 fluctuations were identified. departmental bulletin paper